Simulation of phase separation phenomenon using lattice boltzmann methods - Mohd Suhaimi, Tambong (2009)
This thesis deals with the simulation of the phase separation of two phase flow. The lattice Boltzmann methods is one of the alternative technique to solve multiphase problem such as phase separation of two-phase flow. A derivation of the Lattice Boltzmann scheme from the classical Boltzmann equation is discussed in detail. According to the problems, a single component multiphase (SCMP) LBM is used or involved in the equation in order to solve more phase of fluids. Before that, investigation on non ideal fluid is discussed using Van der Waals fluids where the critical constant of pressure, volume and temperature is solved. By doing this, it will tell the characteristic of the liquid and gas phase. From the Maxwell equal area construction, the value of macroscopic variables, density of fluids is determined which will be code in the algorithm. The source code of the phase separation generate by considering certain criteria. The result of simulation generate from the code prove the precise of the LBM. The 101x101 lattice was used and it is proven that the phase separation formed within the time increased. It is separated into two parts of colour that described the different properties of fluid phase. This project proven the LBM is the best way to simulate phase separation.